Density and Conversion in Biodiesel Production with Supercritical Methanol - Velez, Alexis (2010)
The densities of reacting mixtures of vegetable oils methanol were measured by loading a closed vessel with a known amount of an oil/alcohol mixture of a given molar ratio. For each studied condition, the mixture was brought to a temperature at which the system became homogeneous. The isochoric (constant-volume) relation between temperature and pressure at this particular density and composition was recorded. In the temperature range of 550-630 K, a high conversion of the oil to the corresponding fatty esters and glycerin was obtained. The densities of sunflower oil with methanol for two different alcohol/oil ratios, namely, 40:1 and 25:1, were measured. Densities of coconut oil methanol and methyl oleate methanol mixtures were also measured. The effect of global density on conversion was studied at long reaction times (3-4 h). Strong evidence of the phase transitions of the reacting mixtures, from heterogeneous to homogeneous, was obtained from the experimental results.